Cotton and race in the making of America : the human costs of economic power - Dattel, Eugene R. (Lanham, MD : Ivan R Dee, 2011)
"For more than 130 years, from the early nineteenth century until the mid-twentieth, cotton was the leading export crop of the United States. And the connection between cotton and the African-American experience became central to the history of the republic. America's most serious social tragedy, slavery and its legacy, spread only where cotton could be grown. Both before and after the Civil War, and well into the twentieth century, blacks were relegated to work the cotton fields. Their social and economic situation was aggravated by a pervasive racial animosity and fear of a black migratory invasion that caused white Northerners to contain blacks in the South. Gene Dattel's pioneering study explores the historical roots of these central social issues. In telling detail, Mr. Dattel shows why the vastly underappreciated story of cotton is a key to understanding America's rise to economic power. When cotton production exploded to satiate the nineteenth-century textile industry's enormous appetite, it became the first truly complex global business and a driving force in U.S. territorial expansion and sectional economic integration. It propelled New York City to commercial preeminence and fostered independent trade between Europe and the United States, providing export capital for the new nation to gain its financial "sea legs." And without slave-produced cotton, the South could never have initiated the Civil War, America's bloodiest conflict. Cotton continued to exert a powerful influence on both the American economy and race relations in the years after the Civil War. Mr. Dattel's skillful historical analysis identifies the commercial forces that cotton unleashed and the pervasive nature of racial antipathy it produced. This is a story that has never been told in quite the same way before, related here with the authority of a historian with a profound knowledge of international finance."--Publisher's description.
Slavery in the making of the Constitution -- The silent issue at the Constitutional Convention -- The engine of American growth, 1787-1861 -- Birth of an obsession -- Land expansion and white migration to the Old Southwest -- The movement of slaves to the cotton states -- The business of cotton -- The roots of war -- The North: for whites only, 1800-1865 -- Being free and black in the North -- The colonial North -- Race moves west -- Tocqueville on slavery, race, and money in America -- King Cotton buys a war -- Cultivating a crop, cultivating a strategy -- Great Britain and the Civil War -- Cotton and Confederate finance -- Procuring arms -- Cotton trading in the United States -- Cotton and the freedman -- The racial divide and cotton labor, 1865-1930 -- New era, old problems -- Ruling the freedmen in the cotton fields -- Reconstruction meets reality -- The black hand on the cotton boll -- From cotton field to urban ghetto : the Chicago experience -- Cotton without slaves, 1865-1930 -- King Cotton expands -- The controlling laws of cotton finance -- The delta plantation : labor and land -- The planter experience in the twentieth century -- The long-awaited mechanical cotton picker -- The abdication of King Cotton.
Includes bibliographical references (pages 373-397) and index.
Keywords: Slavery -- Economic aspects -- Southern States -- History; Cotton growing -- Economic aspects -- Southern States -- History; Cotton growing -- Social aspects -- Southern States -- History; Plantation life -- Southern States -- History; African Americans -- Southern States -- Social conditions; United States -- Race relations; United States -- Economic conditions; Slavery -- Political aspects -- United States; United States -- Politics and government -- 1783-1865.; United States -- Politics and government -- 1865-1933.; African Americans -- Social conditions; Cotton growing -- Economic aspects; Cotton growing -- Social aspects; Economic history; Plantation life; Politics and government; Race relations; Slavery -- Economic aspects; Slavery -- Political aspects; Southern States; United States; 1783-1933; History